2020
DOI: 10.1159/000504701
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Inflammatory Bowel Disease

Abstract: a on behalf of Swiss IBDnet, an official working group of the Swiss Society of Gastroenterology

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(77 citation statements)
references
References 62 publications
3
55
2
1
Order By: Relevance
“…A study published in 2020 reports similar results: a lower QoL among women, compared to men diagnosed with IBD [10]. This nding corresponds to data observed in the general population, more precisely a higher rate of absenteeism from work and a more frequent use of health care services among women compared to men [10,11].…”
Section: Discussionsupporting
confidence: 57%
“…A study published in 2020 reports similar results: a lower QoL among women, compared to men diagnosed with IBD [10]. This nding corresponds to data observed in the general population, more precisely a higher rate of absenteeism from work and a more frequent use of health care services among women compared to men [10,11].…”
Section: Discussionsupporting
confidence: 57%
“…Though to date there is no obvious explanation for this difference, it has been suspected that this could be due to genetic, environmental and hormonal differences 3,4 . Notably, in inflammatory bowel disease, it has been suggested that the menstrual cycle specifically impacts disease presentation, course and complications 6 . This finding opens the question and potential to further understand how hormonal differences impact AP presentation and disease course.…”
Section: Discussionmentioning
confidence: 99%
“…Hormonal differences have been seen in PBC, primary sclerosing cholangitis and autoimmune hepatitis, noting that estrogen may play a role in the immune system response 4 . The role of estrogen has proven to be more significant in autoimmune disorders, such as Sjogren's syndrome or PBC, but it is unclear what role it plays in AP 6 . Additional studies to clarify the role of sex biology in AP could help to both triage cases and tailor treatment, as current practices for resuscitation and treatment for AP are uniform for men and women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In human studies, while there are reports of a male predisposition to ulcerative colitis development, these are largely in populations over the age of 45. Our model at 5 weeks in the adult mouse better mimics an earlier onset of disease in humans, where sex‐specific difference in measures of weight loss and colon length are less consistently observed 21,22 . These results provide insights into how the in utero immune environment can influence postnatal susceptibility to disease, and in particular to the development of ulcerative colitis, a condition which has been linked in the past to changes in the maternal environment, but for which there was prior little evidence to support this possibility.…”
Section: Discussionmentioning
confidence: 68%